Resource management for colleges and universities - Massy, William F. (Johns Hopkins University Press, 2020)
"This is a professional title about financing operations at institutions of higher education. The author describes how universities are now using comprehensive activity-based models to understand their teaching and research revenues, costs, margins, and operating details, and he explains how to predict the results of enrollment and other changes as needed in budget planning. He presents detailed narratives about how the new models are being used to inform major university decisions"--